Molecular phylogeny and morphological characterization of Paramicrothyrium bambusae sp. nov. and Tumidispora thailandica sp. nov. from leaf litter - Tennakoon, Danushka S.; Hongsanan, Sinang; de Silva, Nimali I.; Suwannarach, Nakarin; Lumyong, Saisamorn (Phytotaxa, 2023)
During our ongoing studies of fungal diversity on leaf litter, two exciting species were collected from Thailand. Morphological examination coupled with phylogenetic analyses revealed that our species belongs to Paramicrothyrium and Tumidispora in Microthyriaceae. Maximum likelihood, maximum parsimony, and Bayesian analyses of combined internal transcribed spacer (ITS) and large nuclear subunit ribosomal DNA (LSU) sequence data were performed to clarify the phylogenetic affinities of the species. Based on their distinctive morphological traits and phylogenetic support, the new species Paramicrothyrium bambusae and Tumidispora thailandica were introduced. In addition, the new species were compared with phylogenetically and morphologically closely related species, and detailed descriptions, micrographs, and phylogenetic trees of the new species are provided.